Molecular identification of hookworm species infecting free-roaming and owned dogs from an urban area in inner São Paulo State, Brazil - Oliveira-Arbex, Ana Paula; David, Érica Boarato; Bittencourt, Gabriela Nogueira [UNESP]; Babboni, Selene Daniela [UNESP]; Oliveira-Sequeira, Teresa Cristina Goulart [UNESP]; Guimarães, Semíramis [UNESP] (My University, 2022)
Dogs are the most popular pet animals worldwide, but on the other hand, they are main hosts of pathogens potentially transmissible to humans. The aim of this study was to assess the occurrence of intestinal parasites in free-roaming and owned dogs in an urban area in southeastern Brazil and to identify the hookworm species infecting them. Faecal samples (80 from free-roaming and 53 from owned dogs) were examined for intestinal parasites using concentration methods. DNA extracted from hookworm microscopy-positive samples were tested by PCR targeting the ITS1–5.8S–ITS2 region and the amplicons retrieved were sequenced. Intestinal parasites were detected in 43.60% (58/133) of the dogs and hookworm infection was found at the highest prevalence rate (38.30%), followed by Toxocara canis (10.50%), Trichuris vulpis (2.25%), Giardia spp. (0.75%) and Cystoisospora spp. (0.75%). Out of the 51 samples positive for hookworm eggs, 26 (50.90%) were successfully amplified and sequenced. Single infections with Ancylostoma caninum and Ancylostoma braziliense were recorded in 18 (69.20%) and two (7.70%) isolates, respectively, and mixed infections were found in the remaining six samples (23.10%). Both species were found infecting free-roaming and owned animals, but A. caninum was more common. These findings highlight the public health relevance of dogs as reservoirs of zoonotic parasites, with emphasis on hookworm species commonly implicated in cutaneous larva migrans (CLM) in poor and deprived areas.
Keywords: Ancylostoma; dogs; gastrointestinal parasites; hookworms; PCR; zoonosis